Xhubleta: A Heteroglossic Visual Space of Narratives - Arapi, Dorina (Contemporary Southeastern Europe, 2024)
Xhubleta is a traditional dress of the communities of North Albania. A significant aspect of the dress is the visual language of the embroidered patterns on it, and this paper aims to address the visual aspect of them. They have been continuously modified, invented, elaborated by women bearers and subject to their subjectivism, thus shaping different and simultaneous denominations. Comparing the denomination given by the bearers with those given by non-bearers, it is observed different points of view influenced by cultural context, worldview, and interpretations shaped by present-day ideologies propagated through mass media and dominant historical narratives. Drawing on Bakhtin's concept of heteroglossia and the work of A. Smith, this paper argues that the embroidered patterns in xhubleta cannot be simply interpreted as reflections of a historical past, as some non-wearers might wish to interpret them today. Instead, these patterns represent heteroglot, multivoiced realities wherein contradictory meanings of past and present converge within the xhubleta. The fieldwork was conducted in North Albania from 2019 to 2021. In-depth interviews, quantitative observations, and online questionnaires constituted the primary methods used in the analysis. The fieldwork data was then compared to ethnographic accounts provided by Albanian ethnologists, and further supplemented by artefacts and visual data to enrich the analysis.